The role of reactive oxygen species in pressure-dependent myogenic tone - Satirah Zainalabidin,; Paul Coats,; Roger M. Wadsworth, (penerbit ukm, 2012)
Myogenic tone is the response of the vascular smooth muscle to an increase in intraluminal pressure with vasoconstriction and with vasodilation when the pressure is decreased. Such myogenic tone contributes a level of physiological basal tone in response to neurohumoral stimuli. In spite of myogenic tone discovery by Sir William Bayliss 100 years ago, questions still remain regarding the underlying signaling mechanism of the myogenic response. Studies have shown that increased intraluminal pressure or wall tension leads to membrane depolarization, voltage-operated calcium channel (VOCC), stretch-activated cation (SAC) channels, extracelullar matrix (ECM) and actin cytoskeleton. Recently, evidence has shown a potential role for reactive oxygen species (ROS) as a key signalling mediator in the genesis of myogenic tone. The identification of the primary mechanosensors in the initiation of pressure-dependent myogenic tone is essential as these components could be potential therapeutical targets in the future.